A case of Kasabach-Merritt Syndrome in a nine-month-old; a rare complication of haemangioma in the young - Hafiz Khalid Pervaiz; Usman Jamil Mughal; Rai, Izza Ali; Mumtaz Touseef; Aliezeh Fatima Rai (Journal of the Pakistan Medical Association, 2025)
Kasabach-Merritt Phenomenon (KMP) is a life-threatening consumptive coagulopathy that commonly occurs in infants and young children. It is a combination of an enlarging vascular lesion, thrombocytopenia, microangiopathic haemolytic anaemia, and hypofibrinogemia. The case of a nine-month-old child who presented with a tuft haemangioma leading to the clinical features of KMP is presented. The investigation which was performed and pharmacological treatment initiated at different stages of presentation and the characteristic response to treatment are also discussed. Keywords: Haemangioma, Vincristine, Consumptive coagulopathy, KMP, Thrombocytopenia, Haemangioendothelioma.